Functional Aspects of the Solution Structure and Dynamics of PAF, a Highly Stable Antifungal Protein from Penicillium chrysogenum - Batta, Gyula (FEBS J, 2009)
PAF is a promising antimycotic without toxic effects on mammalian cells and therefore may be a drug candidate against the often lethal Aspergillus infections in human. The pathogenesis of PAF on sensitive fungi involves G-protein coupled signaling followed by apoptosis. Here, the solution structure of this small, cationic, antifungal protein from Penicillium chrysogenum is determined by solution NMR. We proved that PAF belongs to the SCOP fold class of its closest homologue AFP from Aspergillus giganteus. PAF comprises five β—strands forming two orthogonally packed β—sheets sharing a common interface. The ambiguity in the assignment of two disulfide bonds of three was investigated by NMR dynamics combined with restrained molecular dynamics calculations. The clue could not be resolved: two ensembles with different disulfide patterns and the one with no S-S bond exhibit essentially the same fold. (15)N relaxation dispersion and interference experiments did not reveal disulfide bond rearrangements via slow exchange. The measured order parameters and the 3.0 ns correlation time is appropriate for a compact monomeric protein of this size. We demonstrated by site-directed mutagenesis that the highly conserved and positively charged lysine-rich domain region on the surface enhances the toxicity of PAF. However, the efficacy of the OB fold is reduced in PAF compared to AFP, due to less solvent exposed aromatic regions explaining the absence of chitobiose binding. The present work lends further support to the understanding of the documented substantial differences between the mode of action of two highly homologous antifungal proteins.